Entrepreneurship - Bygrave, William D.; Zacharakis, Andrew (Hoboken, NJ : Wiley, 2011)
"Entrepreneurs who need to find the solutions to key challenges will turn to Bygrave. The second edition explores the trials and tribulations of entrepreneurship so that they'll have the necessary tools to start their own businesses. It offers new coverage on social enterprises and ethics due to the rise in green trends and corporate scandals. A new chapter has been added on entrepreneurial selling that examines how to sell to multiple stakeholders. New case studies have also been added to several chapters to provide more relevant views. In addition, updated examples and references are included to provide entrepreneurs with the most useful information."--
Includes bibliographical references and indexes.
uaj 02/05/13
Loans
Keywords: New business enterprises; Entrepreneurship; Small business